The effect of chitosan ice glazing on the quality of frozen tilapia fillets: microbiological, physicochemical, and sensory characteristics - HELD, Amanda; BUENO, Gabriela Cristina Ferreira; FERNANDES, Natieli Inácio; das CHAGAS, Renata Alves; GOES, Marcio Douglas; de ARAÚJO, Renata Pires; de VARGAS JUNIOR, Fernando Miranda; de OLIVEIRA, Kelly Mari Pires; da SILVA, Maria Ildilene; GOES, Elenice Souza dos Reis (Food Science and Technology, 2024)
We evaluated the effects of adding chitosan to the glazing solution for tilapia fillets on the microbiological, physicochemical, and sensory attributes of these fillets. We froze fresh tilapia fillets and then glazed them with a solution containing chitosan (0.75, 1.50, or 2.25%) or water (control treatment). Hence, there were a total of four treatments, with 52 fillets per treatment. At various times during frozen storage (0, 30, 60, 90, 120, 150, and 180 days), we analyzed pH, color, and thiobarbituric acid reactive substances (TBARSs). We examined the percentage of coating incorporation as well as the centesimal composition and sensory attributes. We observed a linear increase in the incorporation of the coating as the chitosan level increased. The pH showed a significant difference after 30 days, and it showed a linear increase as the chitosan concentration increased. For the color of the fillets, after storage for 30 days, only the intensity of red showed a linear decrease as the chitosan concentration increased, and after storage for 90 days, the luminosity of the fillets decreased linearly. At 90 and 120 days, there was a linear increase in the yellowness of the fillets. Chitosan had no effect on TBARS formation. As the chitosan concentration increased, there was a linear decrease in heterotrophic bacteria in the fillets, regardless of the storage time. The moisture content increased linearly, while the protein decreased linearly, as the chitosan concentration increased. The ether extract and ash contents were not different between the treatments. In the sensory analysis, there was no regression effect for the evaluated attributes; however, the general acceptability of the fillets of the control treatment was superior to glazing with chitosan. We conclude that a glazing solution containing a high chitosan concentration effectively increases coating incorporation and fillet moisture and decreases the presence of bacteria in fillets, without greatly affecting pH or color during freezing for up to 6 months.